Analisis Problematika Pembelajaran Online SDN 1 Kalirejo Kabupaten Malang Dalam Masa Pandemi Covid-19 - Amalia Hernanda; Maharani Putri Kumalasani; Murtyas Galuh Danawati (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The Covid-19 pandemic has made all schools in Indonesia carry out online learning activities, including SDN 1 Kalirejo, Malang Regency. The implementation of online learning does not always run smoothly, but is accompanied by problems that appear one after another. The type of research used is qualitative research. The research technique used is in the form of observation, interviews, and documentation. Subjects in this study amounted to 7 people, including the principal and teachers in grades 1 to grade 6. The results obtained from this study are that problems occur in each class. Online learning problems arise because the implementation of online learning is still something new for all parties who are directly related to education. Online learning is carried out without prior socialization and simulation, but is directly applied in the field. This is what demands school principals, teachers, students, and parents to adapt to the online learning system. It is in this adaptation process that new problems that must be faced by principals, teachers, students, and parents emerge. The problems faced by each classroom teacher are also different.